Decision aids to facilitate decision making around behavior change in the field of health promotion: A scoping review. Issue 6 (June 2021) - Gültzow, Thomas; Zijlstra, Daniëlle N.; Bolman, Catherine; de Vries, Hein; Dirksen, Carmen D.; Muris, Jean W.M.; Smit, Eline S.; Hoving, Ciska
Highlights: Most identified DAs focused on substance use, primarily on smoking (cessation). Additional (mostly behavior change) intervention elements were often included. Around 70% of the studies reported theory use. Identified behavioral effects of DAs were mixed but potentially promising. Abstract: Objective: To broadly synthesize literature regarding decision aids (DAs) supporting decision making about diet, physical activity, sleeping and substance use a scoping review was performed. Methods: Multiple sources were used: (1) Scientific literature searches, (2) excluded references from a Cochrane review regarding DAs for treatments and screenings, and (3) results from additional searches. Interventions had to (1) support informed decision making and (2) provide information and help to choose between at least two options. Two researchers screened titles and abstracts. Relevant information was extracted descriptively. Results: Thirty-five scientific articles and four DAs (grey literature) were included. Results were heterogeneous. Twenty-nine (94%) studies described substance use DAs. All DAs offered information and value and/or preference clarification. Many other elements were included (e.g., goal-setting). DA's effects were mixed. Few studies used standardized measures, e.g., decisional conflict (n = 4, 13%). Some positive behavioral effects were reported: e.g., smoking abstinence (n = 1). Conclusions: This research shows only some positive behavioral effects of DAs. However, studies reported heterogeneous results/outcomes, impeding knowledge synthesis. Areas of improvement were identified, e.g., establishing which intervention elements are effective regarding health behavior decision making. Practice implications: DAs can potentially be beneficial in supporting people to change health behaviors – especially regarding smoking.